Tanggung Jawab Hukum Bidan Praktik Mandiri Terhadap Penyimpanan Vaksin Imunisasi Anak - Silfiyyah Yunilia (DE LEGA LATA: JURNAL ILMU HUKUM, 2021)
Immunization is a process to make someone form certain antibodies against a disease. A cold chain that is properly managed will have a big effect on the success of immunizations. However, vaccine storage errors also cause severe trauma to children and parents especially if Kipi is heavy to make children lose many things. The formulation of the issues to be discussed in this research is the authority to administer the vaccine for the immunization program to the midwife of independent practice, and the legal responsibility of the midwife for the storage of child immunization vaccines that pose risks. The research methodology used in this study is normative juridical with statutory and conceptual approaches. Based on the foregoing, the conclusion and result of this study is that a higher safety standard for storage and administration of immunizations is needed because midwives gain authority in administering and storing vaccines in independent practice areas with predetermined requirements. Midwives are responsible for reporting up to Kipi handling one of them regarding the costs to be borne by the government. Meanwhile, the form of midwife legal sanctions against the presence of Kipi due to improper vaccine storage is subject to administrative sanctions, revocation of licenses to criminal. So, midwives are expected to understand good cold chain maintenance and be able to provide maximum education in order to minimize the occurrence of Kipi.